High energy density of all-screen-printable solid-state microsupercapacitors integrated by graphene/CNTs as hierarchical electrodes. Issue 20 (9th May 2019) - Chih, Jui-Kung; Jamaluddin, Anif; Chen, Fuming; Chang, Jeng-Kuei; Su, Ching-Yuan
Abstract : An all-screen-printable method for fabricating all solid MSCs by graphene/CNTs hybrid electrodes, where the method shows features of a facile and scalable route to assemble MSCs with high energy density and excellent cyclic stability. Abstract : Microsupercapacitors (MSCs) are alternative power sources that have the potential to fulfill the increasing demand for wearable and on-chip electronics as they are small and lightweight, and show extremely high charge–discharge rates and power densities, and have high flexibility. However, the critical challenge of recent MSCs is the limitation of low energy density and complicated fabrication processes that are high cost and time-consuming. Here, we reported an all-screen-printable method for fabricating all-solid (including electrolytes) and flexible MSCs by rationally designed composite electrodes with electrochemically exfoliated graphene (ECG) and long single-walled carbon nanotubes (CNTs). This method demonstrated to be a facile and scalable route to fabricate and assemble MSCs in a cost-effective manner and with high throughput. As a result, the resulting MSC devices exhibit an areal capacitance of 7.7 mF cm −2 and volumetric capacitance of 77.3 F cm −3, with an excellent cyclic stability of >99% after 15 000 cycles; this can be attributed to the creation of a high diffusion path and the promotion of ion transport capability. The cell exhibits energy and power densities of 10.7 mW h cm −3 and 3.17 W cm −3, respectively. Moreover, there was negligible degradation in capacitance when subjected to bending deformation with radius reduced to 0.5 mm, indicating excellent mechanical flexibility and operation stability. Further, the output voltage and current can be rationally designed by multiple connections of MSC devices in series and parallel to fulfill the demands of various applications. This study provides a scalable and cost-effective method to produce solid-state MSCs with high energy density, which paves the way for their applications in potential wearable devices.